To Study Selective Transport of Ag(I) Ion Using Polymer Inclusion Membranes Containing Thiuram Sulphide as a Carrier - Shipra (My University, 2009)
This work studies the mechanism of active transport of silver (I) through a polymeric inclusion membrane containing Thiuram sulphides having sulphur donor atoms namely Tetramethyl thiuram monosulphide (TMTMS) and Tetraethyl thiuram disulphide (TETDS). Membrane transport studies were performed in a two compartment cell. The CTA/2-NPOE containing thiuram sulphides membrane exhibited uphill transport of silver (I) against concentration gradient. The influences of the aqueous and membrane components on the permeability of silver (I) were studied to show its transport phenomenon. In the presence of thiosulphate ion as a suitable stripping agent in the strip solution, transport of silver occurs almost quantitatively after 120 min with recovery efficiency of 90 ± 4%.
M.Sc. (Chemistry)
Keywords: CTA; Thirum sulfide